2008
DOI: 10.1002/jso.21203
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide outcome registrations to improve quality of care in rectal surgery. An initiative of the European society of surgical oncology

Abstract: In recent years there have been significant improvements in rectal cancer treatment. New surgical techniques as well as effective neoadjuvant treatment regimens have contributed to these improvements. Key is to spread these advances towards every rectal cancer patient and to ensure that not only patients who are treated within the framework of clinical trials may benefit from these advancements. Throughout Europe there have been interesting quality programmes that have proved to facilitate the spread of up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 34 publications
1
12
0
2
Order By: Relevance
“…However, although Ghaferi et al [12] have shown that voluntary reporting does not necessarily lead to selection bias, we cannot exclude that a selection bias caused by hospitals not registering all patients may have occurred. However, comparisons with the Netherlands Cancer Registry showed no evidence of selection bias and an overall estimated completeness of the dataset of 93% (www.dsca.nl), which is similar to the Scandinavian audits, and high compared to the National Bowel Cancer Audit Programme in the UK (completeness 68%) and the Belgium Project on Cancer of the Rectum (40%) [13]. It is unlikely that the remaining 7% of all patients would change our results to a great extent.…”
Section: Discussionmentioning
confidence: 68%
“…However, although Ghaferi et al [12] have shown that voluntary reporting does not necessarily lead to selection bias, we cannot exclude that a selection bias caused by hospitals not registering all patients may have occurred. However, comparisons with the Netherlands Cancer Registry showed no evidence of selection bias and an overall estimated completeness of the dataset of 93% (www.dsca.nl), which is similar to the Scandinavian audits, and high compared to the National Bowel Cancer Audit Programme in the UK (completeness 68%) and the Belgium Project on Cancer of the Rectum (40%) [13]. It is unlikely that the remaining 7% of all patients would change our results to a great extent.…”
Section: Discussionmentioning
confidence: 68%
“…Evidence-based benchmarking for the above parameters or a national expanded quality assurance program for a comprehensive evaluation of quality dimensions of hospitals treating patients with esophageal carcinoma, analogous, for example, to the nationwide registration of outcome data for the improvement in quality of care for rectal surgery-an initiative of the European Society for Surgical Oncology (ESSO)-is currently not in existence [65].…”
Section: Discussionmentioning
confidence: 99%
“…These days, surgical complications are, amongst others, increasingly becoming healthcare quality outcome parameters 23 . To ensure uniform documentation and enable interinstitutional comparison, strict definition of complications is required.…”
Section: Introductionmentioning
confidence: 99%